ADJECTIVE AND NOUN CLAUSE LEXICAL DENSITY IN AN ENGLISH TEXTBOOK FOR SENIOR HIGH SCHOOL STUDENTS - Adityo Prawinanto; Barli Bram (English Education Department, 2020)
This paper analyzed the lexical density of the adjective and noun clauses in an English textbook for senior high school students in Indonesia. It aimed to discover whether or not the textbook was suitable for the students in terms of lexical density. The researchers employed a content analysis approach to analyze data. There were 116 sentences, containing adjective and noun clauses, which were investigated. The researchers implemented the lexical density theory and the lexical density indicators to determine the average level of the lexical density measurements. Results showed that there were three lexical density levels found in those adjective and noun clauses. The three levels were low, medium, and high. The average level of the lexical density obtained from the adjective and noun clauses in the textbook was 47%, which was categorized as low lexical density. Thus, the researchers concluded that the English textbook for the tenth-grade students published by the Indonesian Government was appropriate for the students.